2011
DOI: 10.1590/s1519-38292011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento e prática sobre os fatores de risco para o câncer de mama entre mulheres de 40 a 69 anos

Abstract: Objectives: to investigate knowledge of and practices regarding risk factors for breast cancer among users of the Family Health Strategy (FHS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
40

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 22 publications
1
21
0
40
Order By: Relevance
“…In contrast, 16 studies on the knowledge and awareness about BC cited mainly previous publications of their own country written in Spanish or Portuguese (p < 0.0001). There were only four studies on the knowledge and awareness that mainly cited literature published in English [24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, 16 studies on the knowledge and awareness about BC cited mainly previous publications of their own country written in Spanish or Portuguese (p < 0.0001). There were only four studies on the knowledge and awareness that mainly cited literature published in English [24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a Brazilian study revealed that the knowledge about risk factors was negatively associated with low educational level and family history of BC 27 .…”
Section: Socio-economic Factors Affect Women's Knowledgementioning
confidence: 95%
See 1 more Smart Citation
“…Acredita-se que, pelo avanço das mulheres no mercado de trabalho e a sobrecarga de atividades domésticas, muitas postergam o cuidado com sua saúde, demonstrando que os conceitos de prevenção e promoção ainda se mostram distante da real valorização da manifestação clínica de uma doença (18) . Ao estudar fatores de risco para o câncer de mama entre mulheres de 40 a 69 anos (19) , os autores afirmaram existir algumas características sociodemográficas que podem estar associadas ao nível de conhecimento das mulheres sobre os fatores de risco para a doença. Além disso, colocaram que a investigação dessas características pode subsidiar a identificação de fatores que as levam a uma maior participação em ações de detecção precoce.…”
Section: Discussionunclassified
“…A neoplasia mamária, em casos esporádicos, pode ser detectada pelo autoexame, sendo sempre necessária a avaliação clínica e a realização de mamografia e/ou ultrassonografia. Os casos irregulares devem ser confirmados por meio da biópsia tecidual 5 . Apesar de exames de ultrassonografia e técnicas mamográficas serem capazes de revelar os contornos suaves dos carcinomas de mama TN, eles nem sempre reproduzem imagens de características intramurais, como necrose e fibrose, típicas desse fenótipo.…”
Section: Introductionunclassified